The three powers of the legal elites: the partisan political trajectories of the Judges of the Brazilian Supreme Court (1988-2013) - Fontainha, Fernando de Castro; Filippo Silva Jorge, Thiago; Sato, Leonardo Seiichi Sasada (Revista de Ciências Sociais, 2018)
The debate of law and politics in academic literature focuses as hard in differentiating both as it does in affirming they are one and the same. To contribute to this debate, we did an analysis of the collective biography of the Brazilian Supreme Court Justices – undeniably part of the national legal elites –, more specifically about their involvement in partisan politics. To that end, we collected data from curricula and other biographic data of every Justice that was a member of the court in between 1988 and 2013, we isolated only the data pertaining in data that we classified as part of partisan politics and we did quantitative and qualitative analysis. After identifying 5 types of common activities, we could categorize their trajectories in three kinds (inexistent, episodic and remarkable). Adding that to historical comparisons, we were able to relativize some of the theories about the Court, such as the idea of continual professionalization of its judges, in detriment of their politization. Other conclusions point to the historical relativization of the concept of professionalization in the legal world and the observation that the lack of involvement in partisan politics may result from a different form of political action that is typical to lawyers.